Private Equity, Jobs, and Productivity - Davis, Steven J.; Haltiwanger, John; Handley, Kyle; Jarmin, Ron; Lerner, Josh; Miranda, Javier (American Economic Review, 2014)
Private equity critics claim that leveraged buyouts bring huge job losses and few gains in operating performance. To evaluate these claims, we construct and analyze a new dataset that covers US buyouts from 1980 to 2005. We track 3,200 target firms and their 150,000 establishments before and after acquisition, comparing to controls defined by industry, size, age, and prior growth. Buyouts lead to modest net job losses but large increases in gross job creation and destruction. Buyouts also bring TFP gains at target firms, mainly through accelerated exit of less productive establishments and greater entry of highly productive ones. (JEL D24, G24, G32, G34, J23, J63, L25)